IMPROVING THE ORGANIZATION OF PASSENGER SERVICE ON THE ROUTE BY USING BUSES OF DIFFERENT CAPACITY - I. M. Ryabovbov; R. Ya. Kashmanov (Вестник СибАДИ, 2019)
Introduction. The authors propose to use a rational distribution of buses, taking into account their passenger capacity and the hours of the day, in order to optimize the operation of the rolling stock (RS) on the route. The usage of RS low-capacity on routes with significant passenger traffic increases the RS need, the load on the transport network and emissions of harmful substances into the atmosphere. Operation of high-capacity buses on routes with low power passenger traffic leads to the large intervals of movement and to the increase of waiting time for passengers. The authors highlight that on the number and type of buses’ determining it is necessary to take into account the city specifics (on the example of Volgograd), such as the presence of only two main streets with three lanes in each direction, adjacent roads through which the routes pass, one lane direction.The length of the city along the Volga river in total is about 90 km, due to the peculiarities of the road network (RN) of the city, any irrational use of the RS leads to a significant load on the road network, and, as a result, to the congestion on the roads. Nowadays the PS is not operated effectively.On most routes of the city the capacity of RS does not correspond to passenger traffic on the route. Possible way to optimize the use of RS is taking into account the daily load on the road network.Materials and methods. The authors studied the technology of the movement organization of the rolling stock on the № 59 route. In order to optimize the transportation process, the authors used the method of determining the buses’ number by hour of the day on the base of the graph-analytical method. Buses of different capacity were used on this route.Results. The resulting distribution of buses made it possible to combine the interests of carriers and passengers, to increase the efficiency of rolling stock and to reduce the load on the road network.Discussion and conclusions. As a result, the authors present the measures for improving the efficiency of the rolling stock. These measures are the main for improving transport services for population.